2021
DOI: 10.21203/rs.3.rs-194285/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Product Demand Forecasting in Ecommerce Based on Nonlinear Autoregressive Neural Network

Abstract: With the rapid growth of the e-commerce business scale, to meet customers' demand for efficient order processing, it is of great significance to establish an order management mechanism capable of responding quickly by accurately predicting product demand. This study used real e-commerce order demand data and established a nonlinear autoregressive neural network (NAR) model after pre-processing methods including down-sampling and data set partition to effectively forecast the demand of products in the next 13 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…This research takes smart bracelets among smart wearable products as a case study, and develops a research framework based on relevant literature, as shown in Fig. 1 [26,27,28]. The research process is mainly divided into two stages: the first stage involves semantic analysis to acquire demand information, while the second stage uses KANO analysis to classify demands and finally summarizes applicable design strategies based on demand classification characteristics.…”
Section: Research Frameworkmentioning
confidence: 99%
“…This research takes smart bracelets among smart wearable products as a case study, and develops a research framework based on relevant literature, as shown in Fig. 1 [26,27,28]. The research process is mainly divided into two stages: the first stage involves semantic analysis to acquire demand information, while the second stage uses KANO analysis to classify demands and finally summarizes applicable design strategies based on demand classification characteristics.…”
Section: Research Frameworkmentioning
confidence: 99%